A INVENÇÃO DE UMA RAINHA DE ESPADA: reatualizações e embaraços na dinâmica política do Maranhão Dinástico - Gonçalves, Maria de Fátima da Costa (2006)
This thesis is on Roseana Sarney Murad s public and political construction, based on electoral campaigns to become federal deputy in 1990, to become governoress of the State of Maranhão in 1994 and, in 1998, to her re-election to this post. These are the moments of major visibility and intensification of public relations which in the meantime stay more subliminal. I take as empirical space what I denominate Dynastic Maranhão and the dynastic practices of the political power exerted by Roseana Sarney Murad. I study the symbolic construction of her authority and I investigate, to the extent possible, the permanence and reupdates of a political practice of regional power which tended to spread towards the center of power, but it still remains regional and regionalized, when it comes to talking about Roseana Sarney Murad s course of action between local region and national sphere. I reflect about political power in Maranhão, aiming to break up with the notion of a homogenous event. I consider it a practical act which creates facts in complex relations, by means of the relations of political sociability, as well as the political dimensions of the time of politics, by the apprehension of the strategies of production and of reproduction of the political domination and the forms of subjection. I strive to analyze the oscillations in the dynamics of the relations and co-relations of strengths in the specific work of reproduction of political domination, which allow to apprehend the equal dynamics in the process of construction and of reconstruction of Roseana Sarney Murad s political image, as well as in the process of maintenance of domination/subjection of the political practices of the Dynastic Maranhão. I take two axes which may be indicative of a shock in the king s castle : in 1994, when Roseana Sarney Murad (PFL/MA) almost lost the elections to the post of State Governoress, confronting in the second turn the candidate Epitácio Cafeteira (PPR); in 2002, when Roseana Sarney Murad was a member of the PFL running for the presidential elections and finds herself forced to give up her candidateship when faced with the so called Lunus scandal , in march of 2002, involving herself and her husband Jorge Murad. I construct my epistemic object crossed by various conjectures until I got to the fundamental question: the semiotic aspects of Roseana Sarney Murad s electoral campaigns, in 1994 and 1998, first going through her inaugural rite in the regional politics when she was elected federal deputy in 1990.